1990
DOI: 10.1121/1.399719
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain analysis of auditory-nerve-fiber firing rates

Abstract: Time-domain analysis of firing-rate data from over 200 fibers from the auditory nerve of cat has been used to estimate the formants of the synthetic-syllable stimuli. Distinct groups of fibers are identified based on intervals between peaks in the fiber firing rates. The large extent of some of these groups--over an octave in terms of characteristic frequency--and the lack of short intervals in the longer-interval groups suggest that the behavior of the nonlinear cochlear filters for these signals is effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 0 publications
3
36
0
Order By: Relevance
“…where coefficients a % À1Á64 and b % 2Á44: Calculated scale values s ASW by equation (13) and measured scale values are in good agreement (r ¼ 0Á97; p50Á01) [27]. These formulas also hold for complex noise [29].…”
Section: Apparent Source Width (Asw)mentioning
confidence: 69%
See 1 more Smart Citation
“…where coefficients a % À1Á64 and b % 2Á44: Calculated scale values s ASW by equation (13) and measured scale values are in good agreement (r ¼ 0Á97; p50Á01) [27]. These formulas also hold for complex noise [29].…”
Section: Apparent Source Width (Asw)mentioning
confidence: 69%
“…Amplitudes of waves (I-IV) of the auditory brainstem response (ABR) reflect the sound pressure levels as a function of the horizontal angle of incidence to a listener [3]. Such neural activities, in turn, include sufficient information to attain the autocorrelation function (ACF), probably at the lateral lemniscus as indicated by F ll ðsÞ and F rr ðsÞ: In fact, the time domain analysis of firing rate from the auditory nerve of a cat reveals a pattern of ACF rather than the frequency domain analysis [13]. Pooled interspike interval distributions resemble the short time or the running ACF for low-frequency component.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1(a) shows peristimulus time histograms (PSTHs) for a five-formant synthetic vowel sound. 4 Sharp boundaries characteristic of synchrony capture are seen between the different CF regions driven by different dominant, formant-region harmonics of the multi-formant vowel. Note that in Fig.…”
Section: Introductionmentioning
confidence: 98%
“…Physiologically, temporal information of sound stimuli in the cochlea is the temporal pattern of firings of each of the characteristic frequency fibers. Research in anesthetized animals has shown that the temporal patterns of firings of single fibers evoked by speech stimuli include information on the formant or formant transition of consonants [9,11,13]. However, spontaneous firing of single fibers during silence are unrecognized.…”
Section: Introductionmentioning
confidence: 99%